2018
DOI: 10.1038/s41467-018-02972-z
|View full text |Cite
|
Sign up to set email alerts
|

Protactinium and the intersection of actinide and transition metal chemistry

Abstract: The role of the 5f and 6d orbitals in the chemistry of the actinide elements has been of considerable interest since their discovery and synthesis. Relativistic effects cause the energetics of the 5f and 6d orbitals to change as the actinide series is traversed left to right imparting a rich and complex chemistry. The 5f and 6d atomic states cross in energy at protactinium (Pa), making it a potential intersection between transition metal and actinide chemistries. Herein, we report the synthesis of a Pa-peroxo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…As for reaction (10), the isomerization energies for reaction (11) plotted in Figure 8 show a trend for the d-block species of a decrease from endothermic for V V to exothermic for Nb V and Ta V . The reaction is endothermic for Pr V , U V , Pu V , and Am V with the order being Pr V > Pu V > Am V > U V .…”
Section: Isomerization Energiesmentioning
confidence: 89%
See 1 more Smart Citation
“…As for reaction (10), the isomerization energies for reaction (11) plotted in Figure 8 show a trend for the d-block species of a decrease from endothermic for V V to exothermic for Nb V and Ta V . The reaction is endothermic for Pr V , U V , Pu V , and Am V with the order being Pr V > Pu V > Am V > U V .…”
Section: Isomerization Energiesmentioning
confidence: 89%
“…[13][14][15][16][17][18][19][20][21] Thorium(IV) can be considered as the first 6d transition metal element, 22 and uranium(IV) as the first true 5f actinide, reflecting decreasing energy of 5f relative to 6d orbitals with increasing nuclear charge. 23 The shift from d-block ThO2 to f-block UO2 2+ suggests that isoelectronic PaO2 + could be intermediate in character, 11,21 raising the issue of whether it is more like a d-block transition metal dioxide or a 5f actinyl. 24 For the 4f lanthanide analogue of Pa, praseodymium, the pentavalent oxidation state has been identified only in gas-phase compounds such as PrO2 + and NPrO.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the radial node effect (meaning the correlation of small radius and no radial node of atomic orbitals, reviewed by Kaupp: Kaupp, 2006 ; Huheey et al, 2014 ; Wang et al, 2020 ), the 5f contraction along the series of elements occurs more slowly than 4f, so that f still contributes to the covalence of protactinium, uranium, neptunium and plutonium, and in special cases of thorium (potentially) and americium, too, as a rule of thumb (Morss et al, 2010 ; Neidig et al, 2013 ; Ortu et al, 2016 ; Liu et al, 2017 ; Vitova et al, 2017 ; Wilson et al, 2018 ). From the common chemical empirical point of view, the elements thorium, protactinium, uranium, neptunium, and plutonium are more akin to the lighter outer transition elements hafnium, tantalum, tungsten, rhenium, and osmium, than to their officially homologous inner transition elements cerium, praseodymium, neodymium, promethium, and samarium.…”
Section: The Blocksmentioning
confidence: 99%
“…In particular, protactinium pentoxide is isostructural with the transition metals Nb and Ta, sharing a closed shell pentavalent oxidation state. 28 In addition, a study on Pa is considered to be a unique opportunity for studying the potential periodic properties of the actinide elements and their compounds with respect to their physics and chemistry, including structure and bonding. Wilson recently reported about protactinium as a potential intersection between the d-transition metals (Nb and Ta) and the 5f actinide elements U, Np and Pu owing to the participation of 5f and 6d orbitals cross in energy.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson recently reported about protactinium as a potential intersection between the d-transition metals (Nb and Ta) and the 5f actinide elements U, Np and Pu owing to the participation of 5f and 6d orbitals cross in energy. 28 Although U, Np and Pu oxide systems are known, a detailed structural study of the layered protactinium pentoxide (Pa 2 O 5 ) has not been systematically reported to date.…”
Section: Introductionmentioning
confidence: 99%